Anti-inflammatory and Analgesic Effects of Polygonum orientale L. Extracts - Gou, Kai-Jun; Zeng, Rui; Dong, Yan; Hu, Qi-Qi; Hu, Huang-Wan-Yin; Maffucci, Katherine G.; Dou, Qi-Ling; Yang, Qing-Bo; Qin, Xu-Hua; Qu, Yan (Frontiers in Pharmacology, 2017)
Background and Purpose: Polygonum orientale L. (family: Polygonaceae), named Hongcao in China, is a Traditional Chinese Medicinal and has long been used for rheumatic arthralgia and rheumatoid arthritis. However, no pharmacological and mechanism study to confirm these clinic effects have been published. In this investigation, the anti-inflammatory, analgesic effects and representative active ingredient compounds of P. orientale have been studied. Methods: Dried small pieces of the stems and leaves of P. orientale were decocted with water and partitioned successively to obtain ethyl acetate and ethyl ether extract of P. orientale (POEa and POEe). Chemical compositions of them were analyzed by UPLC-Q-Exactive HRMS. Anti-inflammatory and analgesic effects of POEa and POEe were evaluated using xylene induced ear edema, carrageenan induced paw edema, Freunds’ complete adjuvant induced arthritis, and formaldehyde induced pain in rat. Their mechanisms of anti-inflammatory and analgesic effects were also studied via assays of TNF-α, IL-1β, IL-6, and PGE2 in serum. Results: UPLC-Q-Exactive HRMS analysis showed that POEa and POEe mainly contained flavonoids including orientin, isoorientin, vitexin, luteolin, and quercetin. Furthermore, anti-inflammatory effects of POEa and POEe were evident in xylene induced ear edema. The paw edema in Freund’s complete adjuvant and carrageenan were significantly (P < 0.05, 0.01) inhibited by POEa (5, 7.5 g/kg). POEe (7.5 g/kg) was significantly (P < 0.05, 0.01) inhibited Freunds’ complete adjuvant induced paw edema and cotton pellet induced granuloma formation. Similarly, POEe significantly (P < 0.05, 0.01) inhibited the pain sensation in acetic acid induced writhing test. POEa (5, 7.5 g/kg) significantly (P < 0.05, 0.01) inhibited formaldehyde induced pain in both phases. POEa (7.5 g/kg) markedly ( P < 0.05) prolonged the latency period of hot plate test after 30 and 60 min. The concentrations of TNF-α, IL-1β, IL-6, and PGE2 were significantly (P < 0.01) decreased by POEa (3.75, 5 g/kg). Conclusion: POEa and POEe have anti-inflammatory and analgesic effects, which was mainly relevant to the presence of flavonoids, including orientin, isoorientin, vitexin, luteolin, and quercetin. The mechanism of anti-inflammatory and analgesic effects of POEa may be to decrease the concentrations of TNF-α, IL-1β, IL-6, and PGE2 in serum.